Caracterização química e microestrutural de alumínio reciclado de embalagem pós consumo de bebidas - CALDAS, Elinaldo Silva (2019)
Environmental responsibility is characterized by a set of attitudes towards sustainable development of the planet, among these attitudes is recycling. The material used in this work was an ingot obtained from aluminum recycling, from post-consumer cans of the beverage industry, recycled AA3004 aluminum alloy series 3XXX. Selective collection was performed in order to obtain the necessary raw material for the metallographic characterization.The samples were properly prepared and analyzed by SEM. An ingot was also obtained after the casting process and after this procedure the ingot was submitted to microhardness and metallography testing through sanding, polishing and chemical etching in order to observe the microstructure of the ingot through the optical microscope, as well as to analyze morphology with the aid of SEM, quantitative chemical characterization through EDS and qualitative analysis of chemical elements using FRX.